Community Perception Surrounding Riung National Park to the Conservation of Komodo Dragon - Blegur, Willem Amu; Djohan, Tjut Sugandawati; Ritohardoyo, Su (SCISCITATIO, 2020)
People on Benteng Tengah, Nangamese and Latung have been living in Flores Island and smaller island nearby Flores, like Ontoloe, long before the establishment of national park. In 1992 and 1996, the government established Nature Conservation of Wolo Tado, Nature Conservation of Riung and Marine Nature Conservation of 17 Pulau. This decision led to government’s policy to prohibit the opening of land by burning. Local people used to open a land for agricultural purpose by setting a fire in order to regenerate the savanna to promoting the growth of young grass leaves. People use young grass to feed their cattle. This prohibition causes the people had to herd their cattle far from they live. As the consequence, threat from Komodo (Varanus komodoensis) to attack cattle is increased and people consider Komodo as pest that has to be terminated. This research aimed to study people’s knowledge about Komodo status as endangered species and its implication. Data were collected from people who lives in Benteng Tengah, Nangamese, and Latung, Regency of Ngada, East Nusa Tenggara. Data were obtained from respondents using interviews and questionnaires. Perception of local people who lives in Benteng Tengah (93%), Nangamese (93%) and Latung (100%) showed that people are aware about Komodo’s habitat vegetation. Good perception on Komodo and habitat vegetation will maintain komodo sustainability.